CFD investigation of sub-cooled boiling flow using a mechanistic wall heat partitioning approach with Wet-Steam properties. (December 2018) - Promtong, M; Cheung, SCP; Yeoh, GH; Vahaji, S; Tu, J
In this paper, the mechanistic wall heat partitioning approach was used to capture the complex heat and mass transfer in sub-cooled boiling flows. In order to accommodate the changes of local variables to be relevant to the physical properties of sub-cooled fluids, the Wet-Steam (IAPWS-IF97) is used as the working fluid. Currently, the approach is evaluated based on the bubble sliding along the wall before lifting-off, which is usually found in the flow boiling situations. In the simulation, the closure mechanistic models, including the fractal analysis, the force balance and the mechanistic frequency, were coupled with the Eulerian–Eulerian two-fluid framework, while the Shear Stress Transport model was used as a turbulent modelling closure. The Multiple Size Group model was introduced to handle the bubble interactions and predict the bubble size distribution. Moreover, the effect of adopting the sub-cooled liquid properties into the modelling was investigated and compared with the experiments over a wide range of flow conditions. Specifically, the predicted void fraction and the sub-cooling temperature near the heated wall were precisely compared with the cases of using the constant-property liquid. Overall, the satisfactory agreements were found between the experiments and the predictions of the liquid temperature, void fraction, interfacial area concentration, Sauter mean diameter and bubble and liquid velocities with the exception of the case of high heat and mass fluxes. To enhance the current prediction accuracy for a situation of having a high superheating temperature, more bubble interactions on the boiling wall, such as merging of the bubbles while sliding, need to be considered. Furthermore, to assess the model capability, this mechanistic approach will be introduced to elucidate the sub-cooled boiling flow in situations of using different fluids in the near future.